Multi-kingdom microbiota and functions changes associated with culture mode in genetically improved farmed tilapia (Oreochromis niloticus) - Zhu, Haojun; Qiang, Jun; Li, Quanjie; Nie, Zhijuan; Gao, Jiancao; Sun, Yi; Xu, Gangchun (Frontiers in Physiology, 2022)
Genetically improved farmed tilapia (GIFT, Oreochromis niloticus) are intensively farmed in China, where most of the yield derives from the pond culture system (PCS). The in-pond raceway system (IPRS) is a new type of highly efficient aquaculture mode, and has been recommended as a novel system for GIFT farming. To determine the effects of these culture modes on the gut microbiome of GIFT, we conducted a 90-day experiment in IPCS and PCS units. The result showed that the composition of gut microbiota in GIFT under IPRS and PCS conditions gradually separated as rearing progressed, with divergent responses by the midgut and hindgut bacteria. The α-diversity in hindgut decreased significantly by day 90, as compared with on day 7 (P < 0.05), with a significantly greater decrease in PCS-reared fish than in IPCS fish (P < 0.05). The α-diversity of microbiota in hindgut remained stable (P > 0.05). The overall dominant gut bacteria were Bacteroidetes, Proteobacteria, and Firmicutes. Rearing mode affected the taxonomic profile of the gut bacteria; in midgut, IPRS samples had more Firmicutes and Fusobacteria compared with PCS samples, but less Proteobacteria, Verrucomicrobia, and Actinobacteria. Firmicutes was enriched in IPRS hindgut, and Fusobacteria was enriched in PCS hindgut. Using random-forest models and LEfSe, we also distinguished core taxa that could discriminate between the gut microbial communities under IPRS and PCS conditions. The genus Cetobacterium was significantly enriched in midgut in IPCS fish, and enriched in hindgut in PCS fish. The genus Clostridium sensu stricto was significantly enriched in both IPCS midgut and hindgut. Analysis with PICRUSt2 software revealed that the culture modes were similar in their effects on the gut microbial metabolic functions. The predicted pathways were significantly enriched in the metabolism class (level 1). Relative abundance of bacterial functions related to amino acid, carbohydrate, energy, cofactors, and vitamin metabolism pathways (level 2) were high, as the metabolic activity of intestinal bacteria is especially active. Overall, this study enhances our understanding of the characteristics of gut microbiota in GIFT under IPCS and PCS culture modes. Moreover, our findings provide insights into the microecological balance in IPRS units.